(untitled) (Journal of Engineering, 2009)
This research deals with a modeling of the heating process of an induction furnace with a conducting ferromagnetic core. This is done by performing a sequential coupling between two types of analysis; the harmonic electromagnetic analysis and the transient thermal analysis in order to furnish a complete numerical simulation of this device. The time elapsed to apply this procedure will be too long and unreasonable because of the consideration of the nonlinearity of the magnetic circuit. This problem is solved by the idea of the "Effective Relative Permeability", which is a constant relative permeability equivalent to the nonlinear one in calculating the eddy current losses. The Finite Element Method (FEM) is considered in order to solve this problem using the "ANSYS "computer package. An efficient coupling program deals with heat treatment procedure for any axi-symmetrical non-linear work piece has been built. The obtained results show a good agreement with the published practical measurements. This algorithm is a computer aided design for a nonlinear induction furnace with rotational symmetry, hence it can be used to design such devices instead of the traditional trial and error, experience dependant, design methods which lead to a costly and time wasting design.